Native American patients' perception and attitude about kidney transplant: a qualitative assessment of patients presenting for kidney transplant evaluation. Issue 1 (28th January 2019) - Keddis, Mira; Finnie, Dawn; Kim, Wonsun (Sunny)
Abstract : Objective: Native Americans suffer from lower rates of kidney transplantation compared with whites. Our goal was to elicit patients' perceptions of and attitudes about kidney transplant and the impact of financial burden and cultural taboos. Design: This is an exploratory qualitative interview study of 12 Native American patients recruited after completion of the kidney transplant evaluation. Setting: Semistructured interviews were conducted. Interviews were coded using inductive methods, followed by interpretive coding by the investigators. Results: Thematic analysis revealed the following themes: (1) experience with kidney transplant education by the healthcare team; (2) cultural beliefs regarding kidney transplant; (3) personal motivation and attitude towards kidney transplant; (4) financial burden of kidney transplant and post-transplant care and (5) attitude about living donation. Most participants were educated about transplant as a treatment option after dialysis initiation. All patients in this study recognised that some taboos exist about the process of organ procurement and transplantation; however, the traditional views did not negatively impact their decision to pursue kidney transplant evaluation. Patients shared the common theme of preferring an organ from a living rather than a deceased person; however, the majority did not have a living donor and preferred not to receive an organ from a family member. Most patients did not perceive transplant-related cost as negatively impacting their attitude about receiving a transplant even for patients with below poverty level income. Conclusions: Native American patients presenting for kidney transplant were less likely to be educated about transplant before dialysis initiation; did not perceive financial burden and cultural beliefs were not discussed as obstacles to transplant. While a living donor was the preferred option, enthusiasm for living donation from family members was limited.